Guinea-Bissau : Land Tenure Issues and Policy Study - World Bank (Washington, DC, 2013)
The present study reports on the Government of the Republic of Guinea-Bissau's efforts to develop a comprehensive strategy for enhancing land rights security and achieving social and economic development objectives. This report is divided into two main parts. The first part summarizes the current state of development of the government s land policy, as well as the legal and traditional framework existing for land tenure security. It further presents the institutional environment and technical conditions regarding the implementation of the land law and general land regulation draft. The second part presents and analyzes the government action plan. Specific recommendations are made concerning the basic structure and main elements of a national land administration and land management program, which could comprise three components: (i) the development of a nationwide cadastral system as the core infrastructure and land administration instrument, (ii) the harmonization and integration of traditional and official right systems and institutions, and (iii) subsidiary support to land management capacities, which are crucial for the implementation of the two previous components. Several cross-cutting issues like gender, conflict management, environmental aspects and sustainable resource management are interlaced with the technical elements of land tenure development and considered throughout the report.